Poesía belga contemporánea: William Cliff - Lorente Carrillo, Yolanda (Anales de Filología Francesa, 2009)
The aim of this article is to introduce a great contemporaneous Belgian poet, his way of seeing the world and of creating poetry always considering his vision of life. He’s an homosexual poet who, since his childhood, has had some difficulties in expressing himself and in understanding where his place in the society was. Thanks to his discovery of the Spanish poet named Ferrater, W. Cliff will describe himself as a poet and will find a place in the lyrical world. He is famous for his clear and precise expression without taboo. His poetry was born thanks to his freedom of speech desire which seems to be a denunciation against this hypocritical society based on lies and rules the Man imposes to himself in order to prevent him from being free. W. Cliff uses classic forms to write his poems full of an overwhelming truth.